(untitled) (Journal of Oriental Studies, 2023)
The recognition of the culture, identity, art, and especially handicrafts of every society is of special importance, therefore, the recognition of Iran’s modern history and unique culture and Iranian society is also related to the recognition of its art and artistic works, and they are expressed in the best and most beautiful way by Iranian women. The History of Iranian Embroidery shows that Iranian art and culture, including handmade arts and crafts, have undergone many changes for thousands of years, but they have never lost their Iranian identity and roots. In this article, the meanings of symbols and patterns used in Iranian embroidery have been presented and their Iranian origin has been discussed.